Editorial | الإفتتاحية - Al-Omran | العمران, Hamad bin Ibrahim | حمد بن إبراهيم; Simmons | سيمونز, Cameron | كاميرون; بن عتيق, حمد بن علي بن محمد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
This is Issue 27 of the “King Fahd National Library” magazine, which we present to researchers in the field of library and information sciences and those interested in it, asking God to find in it what they hope for from the latest global trends in the field of information. | هذا هو العدد 27 من مجلة «مكتبة الملك فهد الوطنية،» نُقدمه إلى الباحثين في مجال علوم المكتبات والمعلومات والمهتمين به، سائلين الله أن يجدوا فيه ما يأملون من أحدث الًاتجاهات العالمية في مجال المعلومات